UNSUR-UNSUR FUNGSIONAL KALIMAT DEKLARATIF VERBAL AKTIF - Rustiati, Rustiati (Widya Warta, 2016)
This research aims to describe semantic roles of functional elements of sentences with mono-transitive active verbs, sentences with semi-transitive active verbs, and sentences with intransitive active verbs. The results of the study show that (1) semantic roles of sentences with mono-transitive active verbs consist of subject, predicate, object, and adjunct. The subject plays the roles as agent, result, experiencer, instrument, factor, cause, fortune, and possessive. The predicate plays the roles as action, process, and acquisition. The  object plays the roles as  undergoer, goal, number, place and purpose. The adjunct plays the roles as  manner, repetition,  time, suddenness, doubt, state, manner, and participant, (2) semantic roles of sentences with semi-transitive active verbs comprise subject, predicate, complement, and adjunct. The subject plays the roles as experiencer, factor, place, new information, instrument, and agent. The predicate plays the roles as state, process, and action. The complement plays the roles as goal, time, quality, agent, and undergoer. The adjunct plays the roles as purpose, place, time, and suddenness, and (3) semantic roles of sentences with intransitive active verbs include subject, predicate, and adjunct. The subject plays the roles as new information, undergoer, participant, number, cause, agent, factor, experiencer, instrument, and result. The predicate plays the roles as process, state, action, and existence. The adjunct plays the roles as  instrument, purpose, receiver, time, place, manner, and direction.